2023
DOI: 10.2147/jir.s401446
|View full text |Cite
|
Sign up to set email alerts
|

Naples Prognostic Score as an Independent Predictor of Survival Outcomes for Resected Locally Advanced Non-Small Cell Lung Cancer Patients After Neoadjuvant Treatment

Abstract: Background The Naples Prognostic Score (NPS) can reflect patient’s nutritional and inflammatory status, which is identified as a prognostic indicator for various malignant tumors. However, its significance in patients with resected locally advanced non-small cell lung cancer (LA-NSCLC) patients who receive neoadjuvant treatment remains unclear so far. Methods A total of 165 LA-NSCLC patients surgically treated from May 2012 to November 2017 were retrospectively investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
1
1
Order By: Relevance
“…In this study, it was found that MLR was correlated with pathological stage, differentiation degree, and M stage, which means that a worse the prognosis of patients, so the results of Zhai and Chen's study are contrary to the results of our study [15]. However, the results of this study and MLR value are similar to MLR's correlation in ovarian cancer [16], colorectal cancer [17], lung cancer [18], and other cancers, so our finding needs to be further demonstrated by multi-center and big data research. The PLR value represents the change between platelets and lymphocytes, and an increase in PLR value indicates the weakening of the anti-tumor function mediated by lymphocytes, Int J Clin Exp Pathol 2024;17(5):165-172 which is conducive to the growth and metastasis of tumor [12,19].…”
Section: Discussioncontrasting
confidence: 67%
“…In this study, it was found that MLR was correlated with pathological stage, differentiation degree, and M stage, which means that a worse the prognosis of patients, so the results of Zhai and Chen's study are contrary to the results of our study [15]. However, the results of this study and MLR value are similar to MLR's correlation in ovarian cancer [16], colorectal cancer [17], lung cancer [18], and other cancers, so our finding needs to be further demonstrated by multi-center and big data research. The PLR value represents the change between platelets and lymphocytes, and an increase in PLR value indicates the weakening of the anti-tumor function mediated by lymphocytes, Int J Clin Exp Pathol 2024;17(5):165-172 which is conducive to the growth and metastasis of tumor [12,19].…”
Section: Discussioncontrasting
confidence: 67%
“…Guo et al evaluated patients with unresectable stage III NSCLC and showed NPS to be an independent prognostic factor for both DFS and OS [37]. Similar results were obtained by Zou et al, who studied NPS in patients with locally advanced NSCLC following neoadjuvant therapy [38]. Both studies included inoperable patients with locally advanced disease.…”
Section: Discussionmentioning
confidence: 68%